Pancasila: Local Indigenous Islamic Character Education In Indonesia - Dali, Zulkarnaen (Madania: Jurnal Kajian Keislaman, 2018)
The diversity of values   in Pancasila is the basic capital for character education as the basis of the strength of the character of the Indonesian. The paper seeks to set up an Islamic character education based on the Pancasila-digging theological values   of Islam with the values   of local traditions, cultures and customs of the archipelago. This study is very important given the fact that so far the character, structure, and methods of character education are too oriented to the West by forgetting even ignoring the ideology and values   of the Nusantara character. The approach in this study is descriptive literature review. By transmitting Pancasila’s values   in family life to children, it will make the children make Pancasila’s views as a teaching doctrine, dogma or philosophy that must be practiced in the life of society. Pancasila’s revitalization and re-actualization as a philosophical and ideological foundation of the implementation of the character education system in Indonesia, including the implementation of national character education, cannot be negotiable. This is so that Pancasila can be actualized in everyday life within the family, school, community and in the life of nation and state as an educational process.